Medicinal Plants Use in Prevention and Treatment of Diseases - Abdul Rasool Hassan, Bassam (IntechOpen, 2020)
This book is focused on clarifying the anticancer effects (i.e., apoptotic, antiproliferative, antimetastatic, antiangiogenic) and mechanisms of most of the medicinal plants found in the world against solid and/or hematological cancers.